THE INFLUENCE OF FROTHER IN FLOTATION USING ELECTROLYSIS FOR BATIK DYEING WASTE SEPARATION - Nurrohman, Nurrohman; Warjito, Warjito (Universitas Ibn Khaldun Bogor, 2016)
Batik waste can increase water characteristics such as turbidity, color and Total Suspended Solid (TSS). A technique for separating Batik from the liquid so that its turbidity, color and TSS decrease is needed. Flotation studies have been conducted using electrolysis to produce the bubbles to separate waste synthetic dye staining result of Batik from the bulk liquid. Research carried out by electrolysis with 316L stainless steel electrodes, inside an acrylic pipe with a height of 100 cm, and 8,4 cm in diameter with a voltage 15 V. Solid aluminum sulfate as a reagent was added to coagulate Batik waste as much as 1 gram per 10 ml of Batik waste. Batik waste was mixed with distilled water beforehand. Frother used was pure ethanol as much as 0.1% v/v. From the research it was discovered that flotation of Batik waste can be used for Batik waste separation with the addition of alum. Alum was proved capable of acting as collector in this type of waste separation. Ethanol as frother used was proved capable of making stable froth and increases the separation efficiency.